THE ANALYSIS OF CONCEPT “APOLOGY” IN SISTER CARRIE BY THEODORE DREISER (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
The article discusses the functional and semantic aspects of the term "apology" in “Sister Carrie” by Theodore Dreiser. This work perfectly illustrates the author's literary skills. "Sister Carrie" is the first work of T. Dreiser, describes the author's approach of writing cautiously and thoughtfully in every aspect. Dreiser demonstrates his depth as a stylist and psychotherapist in his debut book. In both the history of American literature and the history of 20th-century realistic fiction worldwide, "Sister Carrie" is regarded as a significant event. The author stressed the semantic and functional aspects of the term "apology" in addition to analyzing the speech act within the parameters of the theory of politeness.